(untitled) (Research, Society and Development, 2020)
The aim of this research is to present contributions and impacts in terms of specialized knowledge to teach Mathematics obtained in MTSK-based research and training actions / projects in Mato Grosso and Mato Grosso do Sul. The theoretical framework Mathematics Teacher’s Specialized Knowledge - MTSK. The methodology is qualitative and documentary, in the region in question, analyzing the actions of two research / training groups (TSK Group and TeiaMat) to understand the contributions and impact with / on MTSK specialized knowledge. In general, the results show that both groups analyzed develop different projects that promote relevant actions, reflections and perspectives for teacher education in the region.